CULTURAL AWARENESS IN EFL PEDAGOGY: A SCOPING REVIEW - Nofyan Fajry Amaruna; Siti Tarwiyah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This scoping review maps 25 studies (2021–2025) on cultural awareness integration in English as a Foreign Language (EFL) contexts using Arksey and O'Malley's framework. Analysis identified four central themes: materials and curriculum representation, teacher beliefs and practices, learner perceptions and outcomes, and pedagogical strategies. Findings reveal persistent implementation challenges across all themes. Textbook analyses revealed systematic Western bias, with 70% of cultural content emphasizing target-culture contexts versus 30% local contexts. Teacher studies disclosed significant gaps between stated beliefs and classroom practices, which remained incidental rather than systematic. Learner research demonstrated positive attitudes toward intercultural learning, yet showed limited competence beyond familiar cultural contexts. Methodologically, databases searched included ERIC, Scopus, and Google Scholar using keywords including "cultural awareness in ELT," "intercultural competence in EFL," and "intercultural communicative competence." Qualitative approaches dominated (44% of studies). All reviewed studies were conducted in Indonesian EFL contexts, limiting generalizability. Critical gaps include scarcity of longitudinal designs, limited comparative multi-site research, insufficient experimental studies, concentration on tertiary education (75% of learner studies), and minimal investigation of technology-mediated intercultural learning. Pedagogically, findings indicate two reform priorities. First, curriculum design needs balanced cultural representation and assessment frameworks valuing intercultural competence alongside linguistic proficiency. Second, teacher development requires systematic training in intercultural communicative competence frameworks, particularly Byram's model, integrated with task-based, project-based, and technology-mediated pedagogies. This synthesis provides evidence-based guidance for curriculum designers, teacher educators, and researchers advancing intercultural communicative competence in EFL contexts.